Characterization of Plasma-deposited a-C:H:Si:F:N Films - Lopes, Juliana Feletto Silveira Costa [UNESP] (2021)
Thin a-C:H:Si:F:N films were studied as a function of the partial pressure of SF6 in plasma feed, RSF, together with tetramethylsilane and N2. Deposition rates varied from ∼4 to ∼19 nm.min-1. Surface roughnesses were typically less than 35 nm. Surface contact angles with water droplets, measured using goniometry, were all around 90°. Scanning electron micrography revealed surface particles, probably formed in the gas phase, of typical diameters ∼8 μm. As revealed by Fourier transform infrared spectroscopy and energy dispersive x-ray spectroscopy, the films are plasma polymers with a carbon and silicon network. Most of the films contain ∼ 60 at.% C, ∼ 10 at.% Si, 20 at.% O and ∼5 to 14 at.% N. Film doping with F rises to ∼2 at.% as RSF is increased. The Tauc gap, calculated from ultraviolet-visible near infrared spectroscopic data, is controllable in the range of ∼3.5 to 4.1 eV by a suitable choice of RSF. Fluorination causes the films to be softer and less stiff. Total deformation and stored energies are reduced compared to those of the film deposited at RSF = 0%. The modulus of dissipation increases from ∼8% to a maximum of ∼65% for the fluorinated films.